The effect of soaking with salicylic acid on some physiological indicators of Chicpea Cicer arietinum L. under conditions of Nacl stress. - شريقي رغداء; وفاء غندور; محمد نجار (Latakia University Journal -Biological Sciences Series, 2024)
This study was conducted in the Ain al-Bayda area in Latakia Governorate, within greenhouses, in the month of November of the year 2020. The aim of this research was to study the effect of soaking the seeds of the chickpea plant, Ghab 4, before planting, with salicylic acid SA, concentration of 100ppm, for 4 hours, on some physiological indicators (wet weight). And dryness of the shoot, relative moisture content in the leaves, estimation of the chlorophyll content in the leaves and estimation of the sodium and potassium content in the leaves and the ratio K+/Na+) under conditions of NaCl stress using concentrations (50, 100, 200) mM. The results showed a clear significant decrease in the average of all previous indicators except for the sodium content of leaves in salt-stressed plants that were not treated with salicylic acid SA. While the interaction between acid and salt led to a significant increase in the previous indicators and a decrease in the sodium content of the leaves. The interference treatment (50mM-100ppm) achieved the best values for these indicators. This confirms the role of salicylic acid SA in improving vegetative and physiological growth characteristics and thus the possibility of chickpea plant growth under conditions of NaCl stress.